THE Future of Work and Lifelong Learning: Education and Upskilling Strategies in the AI Era - Fahmi, Reza; Aswirna, Prima (Proceeding International Conference on Religion, Science and Education, 2026)
The acceleration of digital technology, automation, and artificial intelligence (AI) has reconstructed global labor structures and changed skill requirements across industries. While 85 million jobs are predicted to disappear due to automation, an estimated 97 million new jobs are emerging in data analytics, cybersecurity, Internet of Things, robotics, and the creative sector. These transformations reveal a global urgency: workforce competitiveness will no longer rely solely on formal degrees, but on digital skills, creativity, adaptability, and lifelong learning. However, Indonesia remains behind in digital readiness, curriculum relevance, and industry–education collaboration. This research aims to explore (1) skill gaps between higher education output and future industry needs, (2) factors affecting workforce readiness, and (3) applicable upskilling strategies for Indonesian learners. Using a qualitative–descriptive design, data were obtained through in-depth interviews with lecturers, HR practitioners, government officials, and students. Thematic analysis resulted in five dominant issues: outdated curriculum, lack of innovative learning methods, weak lifelong learning culture, minimal industry involvement, and slow education policies. This study proposes an integration model combining industry-based curriculum, project-based learning, micro-credentials, and professional certification. The model was validated through Focus Group Discussion (FGD), showing its relevance and applicability for universities, vocational institutions, and industry. This work contributes practically to national human capital development and theoretically strengthens the perspectives of Human Capital Theory and Lifelong Learning Theory in the digital era.